Sistem Informasi Pemesanan Barang Berbasis Online Pada PT. Matahari Departement Store Thamrin Plaza - Veronika Lumban Gaol (ADA Journal of Information System Research, 2025)
The development of technology and information through the internet is currently very rapid. The delivery of fast, accurate, and relevant information has become a basic need for companies to support operations and marketing strategies. Technological advances encourage companies to develop information systems that can facilitate the delivery and management of data efficiently. One solution is to design a web-based goods ordering system. This system is expected to provide convenience for companies in marketing products and presenting ordering information in real-time, transparent, and structured. This study was conducted at PT. Matahari Department Store Thamrin Plaza, where the previously used manual system was deemed ineffective in managing customer demand and inventory. In designing this system, the author used the PHP programming language and the phpMyAdmin application for database management, which was run through the XAMPP platform. Meanwhile, MySQL was used as a database to store all goods ordering information systematically. The development of this system was also designed with a user-friendly interface so that it can be easily used by internal company users. In addition, this system supports operational process efficiency, reduces the risk of errors in recording orders, and facilitates managerial decision-making based on available data. By implementing this web-based ordering system, the company is expected to improve the quality of customer service and obtain an information system tailored to its operational needs. If the system operates properly, it will provide added value to PT. Matahari Department Store Thamrin Plaza in terms of efficiency, speed, and accuracy of order processing.